A new brachydactyly syndrome with similarities to Julia Bell types B and E. Issue 3 (June 1985) - Pitt, P; Williams, I
Abstract : We report a family with some of the features of both types B and E Julia Bell brachydactyly. We feel therefore that this family may constitute a new syndrome and we would like to name this after the family involved, the Ballard syndrome.